Critical Infrastructure: Understanding Its Component Parts, Vulnerabilities, Operating Risks, and Interdependencies - Macaulay, Tyson (CRC Press, 2009)
Critical Infrastructure (CI) is a little understood topic, which seems to generate more fear than rational discussion. CI’s are considered fundamental to the functioning of modern economies. Moving beyond definitions, this volume looks at the “iron triangle” within CI: power, telecom, and finance. It introduces the concept of CI’s as industrial and enterprise “risk conductors,” highlighting the fact that a CI failure can propagate an impact throughout an enterprise. This text rethinks the concept of a CI according to contemporary factors, providing guidance for mitigating risk within the framework of national economies.